" The interest of studying Pokémons is to demonstrate that, sometimes, the children are extraordinary competents to learn." - Vitor Casimiro (Universidade Federal de Santa Catarina, 2006)
nterview granted to Journalist Vitor Casimiro, of the Portal he/she Learns Brazil, with the French educator Gilles Brougére, specialist in games and infantile games. In this interview, the educator speaks about the phenomenon of Pokemóns and it criticizes the ignorance, on the part of the adults, of the infantile culture, that it takes them to just see your commercial structure, without analyzing the content.